Hepatitis B virus DNA in patients with HBsAg in south western Nigeria (2012)
There are about 400 million people with chronic hepatitis B virus (HBV) infection worldwide with a potential of adverse sequelae including hepatocellular carcinoma. Recent data have shown that the level of HBV DNA in serum or plasma of an infected person probably reflects more accurately the replicative activity of the virus and therefore may serve as a better maker for management of the infection. This study was designed to determine the rate of detection of HBV DNA in blood samples of patients with HBsAg positive in Nigeria in comparison with the HBe and anti-HBe used widely as serological markers of infectivity. Plasma samples from 105 patients with HBsAg positive were tested for the presence of HBeAg and anti-HBe using a commercial enzyme-linked immunosorbent assay while plasma HBV DNA was quantified using the COBAS Amplicor HBV Monitor assay. Of the 105 HBsAg samples, 17 (16.2%) and 85 (81%) were positive for HBeAg and anti-HBe, respectively, while 8 (7.6%) were negative for both HBeAg and anti-HBe. HBV DNA was detected in 86 (81.9%) of the samples, out of which 15 (18.1%) and 67 (80.7%) were positive for HBeAg and anti-HBe, respectively. HBV DNA was detected in 78.4% of the HBeAg negative samples and in all the eight samples that were negative for both HBeAg and anti-HBe. The implication of these findings in the management of patients with HBV infection is compelling.